Traditional Cultural Landscapes Revisited: Classification, Diversity, Services, and Their Restoration - Zerbe, Stefan (DIE ERDE – Journal of the Geographical Society of Berlin, 2025)
Due to urbanization, land-use intensification as well as land abandonment, traditional cultural landscapes are continuously declining worldwide. However, those landscapes often exhibit a high biodiversity and can provide numerous ecosystem and landscape services. Accordingly, traditional cultural landscapes with their low-input land-use systems might act as a blueprint for sustainable land use and landscape development. Against this background, a classification of traditional cultural landscapes is suggested as a basis for further research and for environmental or rural development policies. This is based on a holistic understanding of landscapes and cultural landscapes, respectively, and the perception of traditions. The criteria for the classification of traditional cultural landscapes encompass prevailing land-use types (e.g., pastures, agroforestry systems), particular land-use practices in order to overcome natural limitations for land use (e.g., terracing of slopes, irrigation), and/or cultural-historical drivers for long-term landscape development (e.g., impact of monasteries). The value of traditional cultural landscapes for nature conservation and sustainable rural development is given through ecological/environmental, social, and economic multifunctionality and multifaceted landscape services. Through their often embedded indigenous and local (ecological) knowledge, they can also contribute to current environmental and socio-economic challenges such as climate change adaptation. A global Red Books of Threatened Landscapes, already suggested in the 1990ies, could support national and international environmental and rural development policies. The restoration of traditional cultural landscapes will not only contribute positively to biodiversity on all levels and the re-establishment of lost or degraded ecosystem and landscape services but will also promote sustainable social-ecological systems.